Macrofaunal biodiversity associated with different developmental phases of a threatened Mediterranean Sabellaria alveolata (Linnaeus, 1767) reef. (March 2019) - Bonifazi, Andrea; Lezzi, Marco; Ventura, Daniele; Lisco, Stefania; Cardone, Frine; Gravina, Maria Flavia
Abstract: Sabellaria alveolata is an ecosystem engineer species capable of building bioconstructions, playing a key functional role in the shallow coastal ecosystems. S. alveolata reefs perform several ecosystem services, such as hosting a rich fauna and producing structures able to provide coastal protection. Despite their ecological role, these bioconstructions have been poorly investigated in the Mediterranean Sea. In this study, the largest Mediterranean S. alveolata reef, located along the Latium coast, was recorded and an habitat mapping duly carried out. During a one-year study, the balance between reef status and associated fauna was investigated using a multidisciplinary approach, the different phases in the annual cycle of S. alveolata were detected and the reef's influence on the diversity of associated macrofauna was assessed. The retrograding phase was detected in September, due to the damages by trampling disturbance, while the growing phase began in March. The comparison with the fauna of the adjacent substrates was also performed, demonstrating that the reef supported a high diversity of associated fauna and qualifying the reef as a biodiversity hotspot. Aimed at improving knowledge of Mediterranean reefs, our study lays the basis for more effective management plans and protection strategies for the threatened biogenic habitats. Highlights: The largest documented Sabellaria reef in the Mediterranean Sea was mapped. The main reef features were investigated by using a multidisciplinary approach. The different phases in the annual cycle of Sabellaria alveolata were detected. This study highlights as Sabellaria alveolata reefs are biodiversity hotspots.